Clinico-pathological evaluation and biomarkers expression associated with back pain in horses - Musa, Mayaki Abubakar (2021)
Back pain is among the most common causes of poor performance in athletic and riding horses. Currently, there is lack of suitable approach for the evaluation of back pain (BP) in horses, thus, there is need to develop quantifiable and objective means to diagnose the condition. Therefore, the main objective of this study was to evaluate clinico-pathological changes and grading, and biomarkers expression associated with BP in horses. The investigation comprised of a retrospective study on 181 cases of equine BP referred to the University Veterinary Hospital, Universiti Putra Malaysia between years 2002 and 2017, development of a grading system based on spinal abnormality-associated clinical features and determination of spinal pathological changes in horses with BP. Immunochemical staining method was used to determine the expression of glial fibrillary acidic protein (GFAP), and ionized calcium-binding adaptor molecule 1 (Iba-1) in the spinal cord to demonstrate gliosis, while ELISA was used to determine the serum concentrations of pNF-H, GFAP, and Iba-1 as potential biomarkers of equine BP. Back pain in the horses were centred at the area under the saddle between T8 and L5 vertebrae. Most horse suffered from primary type (92.27%) of BP, with the main causes, in order of frequency, being soft-tissue lesions (57.48%), vertebral lesions (18.56%), tack-associated (16.77%), and neurological lesions (7.19%). Fourteen horses were graded for severity with BP using response to pain on palpation, muscular hypertonicity, joint stiffness, and physical dysfunction as differentiating parameters. The horses, in order of frequency, suffered from mild-moderate, mild, moderate, and severe BP. The common clinical features that differentiated between horses with and without BP were poor hindlimb impulsion (85.7%), longissimus dorsi spasm at palpation (78.6%), paravertebral muscle stiffness (64.3%), and resistance to lateral bending (64.3%). Spinal cord gross and histopathological investigations on three horses with BP showed kissing spines involving 6 to 9 vertebrae, haemorrhagic malacic lesions with medullary disintegration, degenerative nerve fibres, dilated myelin sheaths, myelin macrophages, axonal swelling and/or loss, and satellitosis. The horses also showed reactive microgliosis and astrogliosis, suggesting that these changes play an important role in development and progression of equine BP. The most common active microglia in horses with BP were the elongated phenotype. This study also reported, for the first time, the presence of hypertrophied microglia phenotype in the spinal cords of horses with lameness. Serum from horses with BP, concurrent BP and lameness, lameness only and healthy horses were used to determine serum pNF-H, GFAP, and Iba-1 concentrations as potential biomarkers in the diagnosis of equine BP. Based on the normal serum creatine kinase and aspartate aminotransferase concentrations, the BP in these horses was not due to muscle disorder. The high serum pNF-H concentration in horses with BP and its good discriminatory capacity in the detection of axonal loss and degeneration suggest that this analyte is a good biomarker for determination of BP in horses. Serum Iba-1 and GFAP concentrations vary considerably among groups of horses; however, the concentration of these serum biomarkers were higher in BP horses than either those with concurrent BP and lameness, lameness or healthy horses. In conclusion, this study showed BP in horses is mainly caused by soft-tissue lesions and kissing spine syndrome, and can be diagnosed and graded using clinical abnormalities - pain response to plapation, muscle hypertonicity, joint stiffness and physical dysfunction. The typical pathological features of the vertebral and spinal cord in equine BP are kissing spines, haemorrhagic myelomalacia, axonal degeneration and reactive astrocytosis and microgliosis. Serum GFAP (cut-off: >0.690 ng/mL) and Iba-1 (cut-off: >26.99 pg/mL) have high diagnostic capacity to differentiate between equine BP due to spinal disorders and other causes.